A Once Charitable Enterprise : Hospitals and Health Care in Brooklyn and New York, 1885-1915 - Rosner, David, 1947- (Book collections on Project MUSE., 1987)
This work, examines the transformation of American hospitals from a series of community- based charitable institutions into the large, bureaucratic system that existed by the end of the Progressive era. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.